Upaya Pemerintahan Dalam Pembaruan Hukum Administrasi Perkawinan (Telaah Pandangan Euis Nurlaelawati) - Kasmoro Wijoyo (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
Marriage registration is one of the legal products issued by the government as an effort to respond to reforms in Islamic law, especially in the field of Islamic Family Law. This update has given rise to debate among experts and the public regarding the interpretation of the marriage registration regulations themselves. This debate ultimately has implications for the order of practice that occurs among society. Regarding the discourse regarding the interpretation of registration regulations, Euis Nurlaelawati has an understanding of thought patterns starting from aspects of interpreting marriage registration regulations as well as sociological aspects that occur in society. This research is operational by carrying out field research which explores information on the expert's understanding (Euis Nurlaelawati) regarding the issue of marriage registration, both the results of Euis Nurlaelawati's views expressed in book or journal form as well as conducting direct interviews with Euis Nurlaelawati. Researchers in analyzing Euis Nurlaelawati's views use progressive legal theory as a method in the legal sociology approach. The results of this research are that in Euis Nurlaelawati's view it falls into the category of progressive legal perspective. This can be seen when Euis Nurlaelawati, in understanding marriage registration regulations, does not only look at the text contained in the legislation but also looks at aspects that occur in upper society. Pencatataan perkawinan merupakan salah produk hukum yang dikeluarkan oleh pemerintah sebagai upaya merespon adanya pembaruan hukum Islam khususnya dibidang Hukum Keluarga Islam. Adanya pembaruan ini memunculkan terjadi perdebatan dalam kalangan para ahli, masyarakat dalam menafsirkan regulasi pencatataan perkawinan itu sendiri. Perdebatan ini akhirnya berimplikasi pada tatanan praktek yang terjadi dikalangan masyarakat. Atas diskursus terkait penafsiran regulasi pencatatan tersebut, Euis Nurlaelawati memiliki pemahaman pola pikir mulai dari aspek penafsiaran regulasi pencatatan perkawinan maupun aspek sosiologis yang terjadi dimasyarakat. Penelitian ini bereperasional dengan dilakukan dengan field research yang menggali informasi atas pemahaman ahli (Euis Nurlaelawati) terhadap isu pencatatan perkawinan baik hasil pandangan Euis Nurlaelawati yang dituangkan dalam bentuk buku ataupun jurnal serta melakukan wawancara langsung kepada Euis Nurlaelawati. Peneliti dalam menganalisis terkait pandangan Euis Nurlaelawati ini menggunakan teori hukum progresif sebagai metode dalam pendekatan sosiologi hukum. Adapun hasil penelitian ini adalah bahwasanya dalam pandangan Euis Nurlaelawati masuk dalam katagori cara pandang hukum progresif. Hal ini terlihat ketika Euis Nurlaelawati dalam memahami regulasi pencatatan perkawinan tidak hanya melihat teks saja yang ada diperundang- undangan melainkan melihat juga pada aspek yang terjadi dimasyakat atas.